Are shocks becoming more frequent or intense? - Zseleczky, Laura; Yosef, Sivan (International Food Policy Research Institute, 2014)
Policymakers, practitioners, and researchers frequently cite an increase in shocks around the world as a reason for focusing on resilience. But have shocks actually increased or become more severe and far-reaching? What does the landscape of shocks look like? Shocks are external, short-term deviations from long-term trends—deviations that have substantial negative effects (which may be short-lived or long lasting) on people’s state of well-being, level of assets, livelihoods, safety, and ability to withstand future shocks. Many shocks are unexpected, but in some cases, such as drought or conflict, the shock may be expected year after year although the individual, community, or system lacks the resilience to prepare for or mitigate it. In other cases, such as climate change, the general shock could be expected but the effect on a particular individual, community, or area could be unexpected.